Caries dental no tratada y percepción de condiciones orales sobre calidad de vida en niños: Untreated dental caries and perception of oral conditions on quality of life in children - Ccanto-Coanqui, Anahis (2022)
Objective: to determine the relationship between untreated dental caries and the perception of quality of life in children aged 8 to 10 years treated at the Pediatric Dentistry Service of the Central Military Hospital, Lima-Peru. Materials and methods: observational, descriptive, prospective and cross-sectional. The sample consisted of 182 children who were selected by non-probabilistic sampling according to the investigator's criteria (children between 8 and 10 years of age, who had agreed to participate in the study and whose parents signed the informed consent); thus, untreated dental caries was evaluated with the pufa/PUFA index and the perception of oral conditions on quality of life with the Child OIDP questionnaire; the data was analyzed using the SPSS version 25 program and the Pearson Chi-square test was used to test the hypothesis. Results: 75,8% of the children had at least one pulpitis, ulceration, fistula or abscess; the most perceived annoyances were the presence of carious teeth 100%; discomfort due to tooth eruption 99,5% and toothache 76,4%; with X2=13,877 and p=0,008, the presence of a significant relationship between the clinical consequences of untreated dental caries and the perception of oral conditions on quality of life is statistically verified. Conclusion: a high percentage of children presented clinical complications of dental caries with a severe perception of oral conditions on quality of life.